If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 2 + -1 = 5x + 11 Reorder the terms: 2 + -1 + 3x = 5x + 11 Combine like terms: 2 + -1 = 1 1 + 3x = 5x + 11 Reorder the terms: 1 + 3x = 11 + 5x Solving 1 + 3x = 11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 1 + 3x + -5x = 11 + 5x + -5x Combine like terms: 3x + -5x = -2x 1 + -2x = 11 + 5x + -5x Combine like terms: 5x + -5x = 0 1 + -2x = 11 + 0 1 + -2x = 11 Add '-1' to each side of the equation. 1 + -1 + -2x = 11 + -1 Combine like terms: 1 + -1 = 0 0 + -2x = 11 + -1 -2x = 11 + -1 Combine like terms: 11 + -1 = 10 -2x = 10 Divide each side by '-2'. x = -5 Simplifying x = -5
| 3+5(4x+6)=2x-3 | | 6/7(y-2)-26/7=4 | | -3x+5+9x=11 | | -2(3-2x)=2(5-2x) | | x+4=-5x+4 | | 3x^2-15x=10 | | -5x+12+8x=3x+3 | | 5y-6=4y+4 | | 3x+30=5x | | D=k+p/2 | | 2/3(4x-7)=-3 | | 3k+2k=6+3k | | 2x-3-4x+5=10 | | 8x+33=3-2x | | 9-3c=36 | | (5/-9)(-2/7)(-3) | | 2x+2=4x-11 | | 60+c=-10 | | 6(2x+3)-3x=63 | | 7y*4.6= | | 20-5c=50 | | 3/4m=-2/3 | | 5/-9x-2/7x-3 | | -3x+7+2x=37 | | 2/3m=3/4 | | (x^2-4)(x^2-4)=-5 | | 3x+7+2x=37 | | 2x+3+2=-1 | | 2x=103+x | | -2(4x-5)=38 | | 10=25+.5x | | 11=5(n-9) |